The Political Economy of Regionalism - Sanjeev Goyal; Klaas Staal (Tinbergen Institute, 2000)
We examine the incentives of regions in a country to unite or toseparate. We find that smaller regions have greater incentives tounite, relative to larger regions. We show, however, that on thewhole, majority voting on separation and union generates excessiveincentives to separate. This leads us to examine the scope ofalternative political institutions and rules in overcoming thepotential inefficiency. Our paper also provides a wide range ofexamples to illustrate the different institutions used in actualpractice to resolve such problems.
Keywords: 330; Regionale Wirtschaftsintegration; Politische Integration; Wahlsystem; Theorie